Pengaruh Invasi Rusia Ukraina terhadap Trading Volume Saham Industri Energi di Bursa Efek Indonesia - Setiawan, Rycki (Universitas Darwan Ali, 2023)
The purpose of this study is to analyze how the Russian invasion of Ukraine may affect stock trading activity for energy companies listed on the Indonesian stock exchange, Sampling was carried out using the technique of purposive sampling, which identified 20 businesses as samples. Data collection covers the time period from 26 November 2021 to 24 May 2022. Trading volume activity was observed 3 days before and 3 days after the invasion, as well as 7 days before and 7 days after the invasion in question. Event study is the focus of this research, which uses multiple analysis of trading volume activity. However, the results of the study and analysis show that the Russian invasion of Ukraine had no significant impact on the trading of energy company stocks on the Indonesian stock exchange, The results indicate that the aforementioned geopolitical policy does not significantly impact trading volume